Comparing the Effectiveness of Emotion-Focused Therapy and Transactional Analysis Therapy on Psychosomatic Vulnerability in Conflicted Women Applying for Divorce - Amrollahi Biuki , Atefeh; Lashgari, Mahdi; Aghaei, Hakimeh (Iranian Journal of Neurodevelopmental Disorders, 2026)
Purpose: The present study aimed to compare the effectiveness of Emotion-Focused Therapy and Transactional Analysis Therapy on psychosomatic vulnerability in conflicted women applying for divorce.Methods and Materials: This applied study employed a quasi-experimental design with a pretest–posttest control group and a three-month follow-up period. The statistical population consisted of conflicted women applying for divorce who were referred by family courts to counseling centers in Tehran. A total of 45 participants were selected using purposive sampling and randomly assigned into two experimental groups (Emotion-Focused Therapy and Transactional Analysis Therapy) and one control group (15 participants in each group). The experimental groups received eight 120-minute intervention sessions, while the control group received no intervention. Data were collected using the Symptom Checklist-25 (SCL-25). Data analysis was conducted using SPSS-26 through descriptive statistics, multivariate analysis of covariance (MANCOVA), repeated measures ANOVA, and Bonferroni post hoc tests.Findings: The results of covariance analysis indicated that Transactional Analysis Therapy had a statistically significant effect on reducing psychosomatic vulnerability (F = 10.21, p = 0.004, η² = 0.274), whereas Emotion-Focused Therapy did not show a significant effect (F = 1.59, p = 0.218). Repeated measures analysis revealed a significant effect of time (F = 7.27, p = 0.008, η² = 0.148) and a significant interaction effect between time and group (F = 4.59, p = 0.042, η² = 0.107), while the main effect of group was not significant (F = 0.62, p = 0.544). Bonferroni post hoc tests showed that Transactional Analysis Therapy was significantly more effective than the control group at posttest (p = 0.016), whereas no significant difference was observed between Emotion-Focused Therapy and the control group (p = 0.664).Conclusion: The findings suggest that Transactional Analysis Therapy is more effective than Emotion-Focused Therapy in reducing psychosomatic vulnerability among conflicted women applying for divorce, with sustained effects over time.